2019
DOI: 10.1080/14678802.2019.1658969
|View full text |Cite
|
Sign up to set email alerts
|

Everyday realities of reintegration: experiences of Maoist ‘verified’ women ex-combatants in the aftermath of war in Nepal

Abstract: Global studies of women's experiences in the disarmament, demobilisation and reintegration (DDR) process have explored its implications for women in the postwar period. Scholars have also already pointed out that ex-combatants in Nepal are facing difficulties in the reintegration period. This paper examines in particular the consequences of the DDR process for so-called Maoist 'verified' women ex-combatants, those who were formally acknowledged as former Maoist combatants and have experienced the entire DDR pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Broadly, much of this research has found that women who committed violence as part of militias or terror organizations often struggle to re-enter society (Mazurana et al, 2017; Hauge, 2020). Though it varies by gendered norms across contexts, women who engaged in violence in Colombia (McFee, 2016), El Salvador (De Watteville, 2002), Guatemala (Weber, 2021), Nepal (Luna, 2019), and Sierra Leone (McKay, 2004), among other places, had particularly difficult reentry and reintegration experiences. Such experiences are not universal, however.…”
Section: Women’s Engagement In Violence and Allocations Of Blamementioning
confidence: 99%
“…Broadly, much of this research has found that women who committed violence as part of militias or terror organizations often struggle to re-enter society (Mazurana et al, 2017; Hauge, 2020). Though it varies by gendered norms across contexts, women who engaged in violence in Colombia (McFee, 2016), El Salvador (De Watteville, 2002), Guatemala (Weber, 2021), Nepal (Luna, 2019), and Sierra Leone (McKay, 2004), among other places, had particularly difficult reentry and reintegration experiences. Such experiences are not universal, however.…”
Section: Women’s Engagement In Violence and Allocations Of Blamementioning
confidence: 99%
“…On the one hand, they still do not know the whereabouts of their loved ones, on the other hand, they still have to fulfil the social expectation of being wives. Likewise, women ex-combatants have met with other challenges in post-conflict Nepal (Luna 2019).…”
Section: Civil War Post-conflict Transition and Peacebuilding In Nepalmentioning
confidence: 99%
“…In the great event of the Battle of Surabaya, the involvement of the common people and women in the jihad was real (Parashar, 2011, p. 295). Women's response to the conflict allowed them to have dual capabilities as housewives while being involved in militant movements, for example, as political activists who sent weapons, ammunition, money, messages, and others (Parashar, 2011;K.C., 2019;Malkasian, 2021). From these two trends, it is evident that women's response to the call for jihad in the 1945 Battle of Surabaya was not the center of attention when viewed comprehensively from the micro side.…”
Section: Introductionmentioning
confidence: 99%